2007
DOI: 10.1073/pnas.0709282104
|View full text |Cite
|
Sign up to set email alerts
|

A specific role of AGS3 in the surface expression of plasma membrane proteins

Abstract: Activator of G protein signaling 3 (AGS3), originally identified in a functional screen for mammalian proteins that activate heterotrimeric G protein signaling, is known to be involved in drug-seeking behavior and is up-regulated during cocaine withdrawal in animal models. These observations indicate a potential role for AGS3 in the formation or maintenance of neural plasticity. We have found that the overexpression of AGS3 alters the surface-to-total ratios of a subset of heterologously expressed plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…A similar distribution is observed for AGS3 upon transfection-mediated expression in various cell types (1,2,17,28). Expression of simply the TPR domain of AGS3 reveals a more prominent nonhomogeneous punctate appearance, whereas expression of the GPR domain reveals a more general, diffuse distribution within the cytosol (28), suggesting that the two domains play dynamic roles in regulating the subcellular distribution of the full-length protein.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar distribution is observed for AGS3 upon transfection-mediated expression in various cell types (1,2,17,28). Expression of simply the TPR domain of AGS3 reveals a more prominent nonhomogeneous punctate appearance, whereas expression of the GPR domain reveals a more general, diffuse distribution within the cytosol (28), suggesting that the two domains play dynamic roles in regulating the subcellular distribution of the full-length protein.…”
Section: Discussionsupporting
confidence: 60%
“…AGS3 is involved in a number of different cellular activities, including asymmetric cell division during neuronal development (30), neuronal plasticity and addiction (9,10,12,38,39), autophagy (27), membrane protein trafficking (17), cardiovascular function (7), and metabolism (7). AGS3 is a multidomain protein consisting of seven tetratricopeptide repeats (TPR) in the amino-terminal portion of the protein and four G-protein regulatory (GPR) motifs in the carboxyl region of the protein.…”
mentioning
confidence: 99%
“…42 Moreover, it has been found that the overexpression of AGS3 alters the surface ratios of heterologously expressed plasma membrane receptors and channels, and affects the internalization or recycling of surface proteins. 43 As mentioned earlier, the small G proteins, such as Ras, Rho and Rab, are the likely downstream targets after activation of these receptors, and there is considerable interest in these proteins both as mediators of myocyte hypertrophy and as therapeutic targets. [44][45][46] Against this background, it is interesting that a significant proportion of the cluster of signal transduction-related genes showing increased expression in late LVH belong to the small GTPase family and included the ras homolog gene family, member Q (also known as TC10 or Rhoq), Rho-associated coiled-coil forming kinase 2 (ROCK2) and RAS-related protein 1a (Figure 3a).…”
Section: Signal Transductionmentioning
confidence: 99%
“…1). In mammalian systems, AGS3 is implicated in asymmetric cell division, neuronal plasticity and addiction, autophagy, membrane protein trafficking, polycystic kidney disease, renal response to ischemia, immune cell chemotaxis, insulin-like growth factor-1 mediated ciliary resorption, cardiovascular regulation, and metabolism (Blumer et al, 2002(Blumer et al, , 2006(Blumer et al, , 2008Ghosh et al, 2003;Gotta et al, 2003;Pattingre et al, 2003;Bowers et al, 2004Bowers et al, , 2008Sato et al, 2004;Yao et al, 2005Yao et al, , 2006Groves et al, 2007;Willard et al, 2008;Groves et al, 2010;Nadella et al, 2010;Vural et al, 2010;Hofler and Koelle, 2011;Regner et al, 2011;Chauhan et al, 2012;Kwon et al, 2012;Conley and Watts, 2013;Kamakura et al, 2013;Yeh et al, 2013). AGS3 single nucleotide polymorphisms are associated with diabetes and glucose handling (Scott et al, 2012;Hara et al, 2014;Huyghe et al, 2013).…”
Section: Activators Of G Protein Signaling (Ags Proteins)mentioning
confidence: 99%
“…2A), function as part of a distinct signaling pathway (e.g., GaGPR signaling module) (Fig. 2B), serve as a chaperone for Ga, and/or impact basic cellular events such as autophagy (Pattingre et al, 2003;Groves et al, 2010;Vural et al, 2010;Garcia-Marcos et al, 2011a) and secretory pathway dynamics (Groves et al, 2007;Oner et al, 2013b).…”
Section: Activators Of G Protein Signaling (Ags Proteins)mentioning
confidence: 99%